Optimium Planning of Hybrid Renewable Energy System Using HOMER - J. B. Fulzele; Subroto Dutt (International Journal of Electrical and Computer Engineering (IJECE), 2012)
A hybrid renewable energy system may be used to reduce dependency on either conventional energy or renewable system. Optimization of hybrid renewable energy systems looks into the process of selecting the best components and its sizing with appropriate operation strategy to provide cheap, efficient, reliable and cost effective alternative energy. In this paper a methodology has been develop for optimum planning of hybrid PV-Wind system with some battergy backup. The local solar radiation, wind data and components database from different manufactures are analyzed and simulated in HOMER to assess the technical and economic viability of the integrated system. Performance of each component will be evaluated and finally sensitivity analysis will be performed to optimize the system at different conditions. Keywords:Optimization, Hybrid system,Renewable system, HOMER, Cost of energy.DOI:http://dx.doi.org/10.11591/ijece.v2i1.157